2021
DOI: 10.1038/s41467-021-21957-z
|View full text |Cite
|
Sign up to set email alerts
|

PGC1/PPAR drive cardiomyocyte maturation at single cell level via YAP1 and SF3B2

Abstract: Cardiomyocytes undergo significant structural and functional changes after birth, and these fundamental processes are essential for the heart to pump blood to the growing body. However, due to the challenges of isolating single postnatal/adult myocytes, how individual newborn cardiomyocytes acquire multiple aspects of the mature phenotype remains poorly understood. Here we implement large-particle sorting and analyze single myocytes from neonatal to adult hearts. Early myocytes exhibit wide-ranging transcripto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 62 publications
2
66
0
Order By: Relevance
“…Dimensionality reduction of our reference with uniform manifold approximation and projection (UMAP) revealed a continuum of maturation from e14 in p56, in concordance with previous results from our group and others [33][34][35] (Fig 1B). As an initial strategy, we considered quantification of maturation status by integration of query datasets with our reference.…”
Section: Scrna-seq CM Reference Captures Maturation-related Changessupporting
confidence: 92%
See 1 more Smart Citation
“…Dimensionality reduction of our reference with uniform manifold approximation and projection (UMAP) revealed a continuum of maturation from e14 in p56, in concordance with previous results from our group and others [33][34][35] (Fig 1B). As an initial strategy, we considered quantification of maturation status by integration of query datasets with our reference.…”
Section: Scrna-seq CM Reference Captures Maturation-related Changessupporting
confidence: 92%
“…At the single cell level, CM maturation proceeds heterogeneously along a unidirectional trajectory [33]. We were therefore curious to know the extent to which entropy score could capture single cell positioning along this trajectory, in effect functioning as a pseudotime metric.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…In addition, ZLN005 treatment increased cell sarcomere length, improved cell calcium handling, and enhanced intercellular connectivity [ 128 ]. Single-cell gene network analysis showed that PGC-1 drives CM maturation via YAP1 and SF3B2 [ 129 ]. All these data indicate that PGC-1 plays as a multifaceted regulator coordinating cellular hypertrophy, contractility, and metabolism of CMs from immature to mature.…”
Section: Mitochondrial Biogenesis and Cardiac Maturationmentioning
confidence: 99%
“…However, mechanistic data confirming the central role of PPARα in perinatal cardiac adaptation are lacking, and further research is needed to determine if PPARα is the only nutrient-sensing effector in this process. Murphy et al recently showed that regulatory networks driven by PPARα through peroxisome proliferator-activated receptor coactivator-1 (Pgc1α) promote the maturation of pluripotent stem cell-derived cardiomyocytes by regulating YAP1 and SF3B2 proteins [133]. During the fetal-to-neonatal transition, neonatal cardiomyocytes progressively lose their ability to proliferate and enter a hypertrophic phase.…”
Section: Pparαmentioning
confidence: 99%